The Effect of Readiness for Change and Digital Mindset on School Counselors’ Intention to use Technology through Digital Competence - zumrotul Hasanah; Sugiyo Sugiyo; Sunawan Sunawan (Study Program of Guidance and Counselling, Post Graduate Program, Universitas Negeri Semarang, 2024)
School counselors' use of technology is substantial and have many substantial effects on treatment. The purpose of this research is to examine how school sounselors' digital competence mediated the relationship between their digital mindset desire to use technology and readiness for change. Researched used correlational design to survey 90 middle school counselors from the Semarang Residency, who were chosen using a quota area random sampling technique. Participants were asked to rate their own level of preaparedness for change, digital mindset, digital competency, and technolgical intention. Data was examined by multiple regression and path analysis. The Sobel test was used to examine the mediation findings. Looking the statistics we can see that digital mindset greatly improves digital competence, and that readiness for change has a major impact on digital competence. Findings also showed that digital competence considerably effcts the intention to use technology, and that digital mindset and readiness for change bith have substantial impacts. In addition, the mediation analysis's findings showed that digital competence explains how digital mindset and openness for change affect technology use intention. School counselors and relevan organizations might use this study's findings to foster digital competence by training school counselors to think digitally and be open to change